Coping Strategies in Post-War Rural Mozambique - Tilman Brück (Deutsches Institut für Wirtschaftsforschung (DIW), 2003)
This paper analyses post-war coping strategies by farm households in developing countries. The analysis is based on a portfolio model of activity choices in war-affected rural Sub- Saharan Africa. A case study using farm household survey data estimates the determinants of agricultural coping strategies in post-war Mozambique. Post-war coping strategies differ from pre- and mid-crisis coping strategies. War-affected households are forced to adopt very risky coping strategies that re-enforce their vulnerability. Households choose between market and non-market forms of exchange and even consider exiting markets entirely. Post-war reconstruction policy should focus on re-capitalizing households, providing public goods and establishing markets.
Keywords: J22; O12; O13; Q12; 330; coping strategies; activity choices; labour allocation; portfolio model; war; conflict; reconstruction; policy; Mozambique; Africa; Landwirtschaftlicher Familienbetrieb; Kriegsschaden; Wirtschaftliche Anpassung; Mocambique